The Study on the Mechanism of Hugan Tablets in Treating Drug-Induced Liver Injury Induced by Atorvastatin - Lv, Shujing; Yu, Honghong; Liu, Xinyue; Gao, Xiaoyan (Frontiers in Pharmacology, 2021)
Atorvastatin is a widely used lipid-lowering drug in the clinic. Research shows that taking long-term atorvastatin has the risk of drug-induced liver injury (DILI) in most patients. Hugan Tablets, a commonly used drug for liver disease, can effectively lower transaminase and protect the liver. However, the underlying mechanism of Hugan Tablets alleviating atorvastatin-induced DILI remain unclear. To address this problem, comprehensive chemical profiling and network pharmacology methods were used in the study. Firstly, the strategy of “compound - single herb - TCM prescription” was applied to characterize the ingredients of Hugan Tablets. Then, active ingredients and potential targets of Hugan Tablets in DILI treatment were screened by network pharmacology, molecular docking, and literature research. In the end, the mechanism of Hugan Tablets in treating atorvastatin-induced DILI was elucidated. The results showed that Hugan Tablets can effectively alleviate DILI induced by atorvastatin in model rats, and 71 compounds were characterized from Hugan Tablets. Based on these compounds, 271 potential targets for the treatment of DILI were predicted, and 10 key targets were chosen by characterizing protein-protein interactions. Then, 30 potential active ingredients were screened out through the molecular docking with these 10 key targets, and their biological activity was explained based on literature research. Finally, the major 19 active ingredients of Hugan Tablets were discovered. In addition, further enrichment analysis of 271 targets indicated that the PI3K-Akt, TNF, HIF-1, Rap1, and FoxO signaling pathway may be the primary pathways regulated by Hugan Tablets in treating DILI. This study proved that Hugan Tablets could alleviate atorvastatin-induced DILI through multi-components, multi-targets, and multi-pathways.